2007
DOI: 10.1167/iovs.06-1008
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Activating Factor Overturns the Transcriptional Repressor Disposition of Sp1 in the Expression ofMMP-9in Human Corneal Epithelial Cells

Abstract: These findings demonstrate that collaboration between several regulatory elements is required for the induction of MMP-9 promoter activity by PAF and that PAF overturns the repressor effect of Sp1 through activation of the MEK/ERK signaling cascade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…The possible involvement of such interaction can not be excluded. Regarding the effect of PAF on Sp-1, Taheri et al [42] reported that PAF directly activates Sp-1 by phosphorylation through ERK MAPK signaling. Our unpublished data also demonstrates that PAF activates ERK, suggesting that PAF is able to activate Sp-1 in H1299 cells via ERK activation, which, in turn, may modulate the physical interaction of Sp-1 with p53 or NF-B.…”
Section: Discussionmentioning
confidence: 99%
“…The possible involvement of such interaction can not be excluded. Regarding the effect of PAF on Sp-1, Taheri et al [42] reported that PAF directly activates Sp-1 by phosphorylation through ERK MAPK signaling. Our unpublished data also demonstrates that PAF activates ERK, suggesting that PAF is able to activate Sp-1 in H1299 cells via ERK activation, which, in turn, may modulate the physical interaction of Sp-1 with p53 or NF-B.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that translocation of the transcription factor to the nuclei induced by PAF prevents epithelial cell apoptosis and also demonstrates a regulatory action of NF-B in PAF-induced apoptosis. Recent experiments have shown that activation of NF-B is required for gene induction of MMP-9 by PAF in corneal epithelial cells ( 117 ).…”
Section: -3 Fatty Acids and Their Derivatives Are Important In The Rementioning
confidence: 99%
“…In the process of cancer invasion, cells can escape from the primary tumor, penetrate into lymphatic and blood vessels, circulate through the bloodstream, and grow into distant foci in normal tissues elsewhere in the body [13]. Cancer cells are involved in numerous interactions with the extracellular matrix and its proteins such as growth factors and cytokines.…”
Section: Discussionmentioning
confidence: 99%